Imaging G-Ratio in Multiple Sclerosis Using High-Gradient Diffusion MRI and Macromolecular Tissue Volume - Yu, F.; Fan, Q.; Tian, Q.; Ngamsombat, C.; Machado, N.; Bireley, J.D.; Russo, A.W.; Nummenmaa, A.; Witzel, T.; Wald, L.L.; Klawiter, E.C.; Huang, S.Y. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Remyelination represents an area of great therapeutic interest in multiple sclerosis but currently lacks a robust imaging marker. The purpose of this study was to use high-gradient diffusion MRI and macromolecular tissue volume imaging to obtain estimates of axonal volume fraction, myelin volume fraction, and the imaging g-ratio in patients with MS and healthy controls and to explore their relationship to neurologic disability in MS.MATERIALS AND METHODS: Thirty individuals with MS (23 relapsing-remitting MS, 7 progressive MS) and 19 age-matched healthy controls were scanned on a 3T MRI scanner equipped with 300 mT/m maximum gradient strength using a comprehensive multishell diffusion MRI protocol. Macromolecular tissue volume imaging was performed to quantify the myelin volume fraction. Diffusion data were fitted to a 3-compartment model of white matter using a spheric mean approach to yield estimates of axonal volume fraction. The imaging g-ratio was calculated from the ratio of myelin volume fraction and axonal volume fraction. Imaging metrics were compared between groups using 2-sided t tests with a Bonferroni correction.RESULTS: The mean g-ratio was significantly elevated in lesions compared with normal-appearing WM (0.74 vs 0.67, P < .001). Axonal volume fraction (0.17 vs 0.23, P < .001) and myelin volume fraction (0.17 vs 0.25, P < .001) were significantly lower in lesions than normal-appearing WM. Myelin volume fraction was lower in normal-appearing WM compared with that in healthy controls (0.25 vs 0.27, P = .009). Disability, as measured by the Expanded Disability Status Scale, was significantly associated with myelin volume fraction (β = –40.5, P = .001) and axonal volume fraction (β = –41.0, P = .016) in normal-appearing WM.CONCLUSIONS: The imaging g-ratio may serve as a biomarker for the relative degree of axonal and myelin loss in MS.AVFaxonal volume fractionEDSSExpanded Disability Status ScaleHChealthy controlsMSFCmultiple sclerosis functional compositeMTVmacromolecular tissue volumeMVFmyelin volume fractionNAWMnormal-appearing white matterNODDIneurite orientation dispersion and density imagingPMSprogressive MSqMTquantitative magnetization transferRRMSrelapsing-remitting MS